Desain Lembar Kegiatan Peserta Didik (LKPD) Berbasis Guided Inquiry pada Mata Pelajaran Kearsipan Kelas X OTKP di SMK PGRI 13 Surabaya - Inayah Inayah; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
This development research is motivated by the absence of Student Activity Sheets for Filing Subjects so that the learning process in the classroom is teacher centered and triggers students to be passive and less active in class. This study aims to describe the design process of Student Activity Sheet (LKPD) based on Guided Inquiry in the Class X Archive OTKP Subjects at SMK PGRI 13 Surabaya. This type of research is the development of Research and Development (R&D) 4D models that are limited to 3D, namely Define, Design and Develope. Data collection instruments in the form of interview guides and LKPD evaluation questionnaires. LKPD is tailored for learning with a scientific approach and to improve student motivation and thinking ability with guided inquiry. The results showed that the design produced in the form of guided inquiry LKPD based on class X OTKP was included in the very feasible category for material and language aspects. After going through several stages of improvement, LKPD was also declared to be interesting and helpful in the learning of students based on the LKPD evaluation results. Thus, LKPD berbasis guided inquiry pada mata pelajaran kearsipan kelas  X  OTKP results of this design is feasible and can be continued to the dissemination  stage and is used by students in the learning of Archives.